Positive electrode active material, positive electrode, and rechargeable lithium battery
By adopting mixed positive electrode active materials of lithium nickel manganese composite oxide and lithium manganese oxide, the problems of high cobalt content and high cost in the prior art are solved, and high capacity, long cycle life and improved high voltage performance are achieved. effect.
Patent Information
- Application Number
- CN202411055804.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-08-03
- Filing Date
- 2024-08-02
- Publication Date
- 2025-02-14
AI Technical Summary
The positive electrode active substances of existing rechargeable lithium batteries contain rare metal cobalt, which is short of supply and high cost, making it difficult to achieve high capacity and high energy density while reducing production costs.
Using positive electrode active substances including lithium nickel manganese composite oxides, the lithium nickel manganese composite oxide particles and lithium manganese oxides of different particle sizes are appropriately mixed to form high capacity, long cycle life and improved high voltage. Performance positive electrode active substance.
It achieves high capacity and high energy density while reducing production costs, ensures long cycle life characteristics, and suppresses side reactions with the electrolyte, improving high voltage performance.
Smart Images

Figure CN119447216A_ABST
Abstract
Description
Technical Field
[0001] One or more embodiments of the present disclosure are directed to a positive electrode active material, and a positive electrode and a rechargeable lithium battery each including the positive electrode active material. Background Art
[0002] Portable information devices (such as cellular phones, laptop computers, smart phones, etc.) or electric vehicles have used rechargeable lithium batteries with relatively high energy density and relative portability as driving power sources. Recently, research has been actively conducted to use rechargeable lithium batteries with relatively high energy density as driving power sources (car batteries) for hybrid vehicles or electric vehicles or as power storage power sources for energy storage systems or power walls (ESS).
[0003] Various positive electrode active materials have been studied to realize rechargeable lithium batteries for these desired applications. Among them, lithium nickel oxides, lithium nickel manganese cobalt composite oxides, lithium nickel cobalt aluminum composite oxides and lithium cobalt oxides are mainly used as positive electrode active materials. However, although the demand and utilization of rechargeable lithium batteries with large size, relatively high capacity or relatively high energy density have increased rapidly recently, the supply of positive electrode active materials including rare metal cobalt is expected to be in serious shortage. For example, because cobalt is expensive and the remaining reserves are limited, it is necessary and / or desirable to develop positive electrode active materials that exclude cobalt or include it in a reduced content (e.g., amount). Summary of the invention
[0004] One or more aspects of the embodiments of the present disclosure relate to: a positive electrode active material including a lithium nickel manganese composite oxide (reducing the price of the positive electrode material, ensuring high capacity and high energy density characteristics, and improving high voltage performance by inhibiting or reducing side reactions with an electrolyte at relatively high voltages) and a positive electrode and a rechargeable lithium battery, each of which includes the aforementioned positive electrode active material. Additional aspects will be stated in part in the subsequent description and in part will be apparent from the description, or can be understood by practicing the presented embodiments of the present disclosure.
[0005] In one or more embodiments, the positive electrode active material includes a first positive electrode active material, a second positive electrode active material, and a third positive electrode active material, the first positive electrode active material includes a lithium nickel manganese type composite oxide having a nickel content (e.g., amount) greater than or equal to about 60 mol% based on 100 mol% of the total metals other than lithium included in the first positive electrode active material and is in the form of a plurality of secondary particles each including a plurality of aggregated primary particles (e.g., prepared by aggregating a plurality of primary particles), the second positive electrode active material is in the form of a plurality of individual particles (e.g., a plurality of individual particles each in the form of a whole particle) of a lithium nickel manganese type composite oxide having a nickel content (e.g., amount) greater than or equal to about 60 mol% based on 100 mol% of the total metals other than lithium included in the second positive electrode active material, and the third positive electrode active material is in the form of a plurality of particles including a lithium manganese type oxide.
[0006] In one or more embodiments, the positive electrode includes a positive electrode current collector and a positive electrode active material layer on the positive electrode current collector, wherein the positive electrode active material layer includes the aforementioned positive electrode active material.
[0007] In one or more embodiments, a rechargeable lithium battery includes the aforementioned positive electrode, negative electrode, and electrolyte.
[0008] The positive electrode active material according to one or more embodiments (whose capacity is maximized or increased while minimizing or reducing production costs) ensures long cycle life characteristics, and its side reaction with the electrolyte at high voltage is suppressed or reduced. Accordingly, a rechargeable lithium battery using the positive electrode active material can exhibit high initial charge and discharge capacity and efficiency under high voltage driving conditions, and can achieve long cycle life characteristics. BRIEF DESCRIPTION OF THE DRAWINGS
[0009] The above and other aspects, features and advantages of certain embodiments of the present disclosure will become more apparent from the following description taken in conjunction with the accompanying drawings.
[0010] Figure 1 is a cross-sectional view schematically illustrating a rechargeable lithium battery according to one or more embodiments.
[0011] Figure 2 is a scanning electron microscope (SEM) image of the first positive electrode active material of Example 1 of the present disclosure.
[0012] Figure 3 : is a SEM image of the second positive electrode active material of Example 1 of the present disclosure.
[0013] Figure 4 and Figure 5Each is a SEM image of a third positive electrode active material of Example 1 of the present disclosure.
[0014] Reference numerals
[0015] 100: Rechargeable lithium battery 10: Positive electrode
[0016] 20: Negative electrode 30: Separator
[0017] 40: electrode assembly 50: shell DETAILED DESCRIPTION
[0018] Hereinafter, example embodiments will be described in more detail so that those skilled in the art can easily implement them. However, the present disclosure may be implemented in many different forms and is not to be construed as limited to the example embodiments set forth herein.
[0019] The terms used in this article are only used to describe the embodiments and are not intended to limit the present disclosure. As used herein, the singular forms "a", "an", and "the" are intended to include the plural forms as well, unless the context clearly indicates otherwise. Further, when describing the embodiments of the present disclosure, the use of "may" refers to "one or more embodiments of the present disclosure".
[0020] As used herein, "combinations thereof" may refer to mixtures, laminates, composites, copolymers, alloys, blends, reaction products, and the like, of the components.
[0021] In this document, it should be understood that terms such as “comprise(s) / comprising”, “include / including” or “have / has / having” are intended to indicate the presence of implemented features, numbers, operations, elements and / or their (e.g., any appropriate) combination, but this does not exclude the possibility of the presence or addition of one or more other features, numbers, operations, elements and / or their (e.g., any appropriate) combination.
[0022] In the accompanying drawings, the thickness of layers, films, panels, regions, etc. may be exaggerated for clarity, and throughout the present disclosure, the same reference numerals represent the same elements, and for the sake of brevity, a repeated description thereof may not be provided. It will be understood that if (for example, when) an element (such as a layer, film, region, or substrate) is referred to as being "on" another element (such as a layer, film, region, or substrate), it may be directly on the other element (such as a layer, film, region, or substrate), or there may also be intervening elements. In contrast, if (for example, when) an element (such as a layer, film, region, or substrate) is referred to as being "directly on" another element (such as a layer, film, region, or substrate), there are no intervening elements.
[0023] In one or more embodiments, the “layer” herein includes not only a shape or film formed on the entire surface but also a shape or film formed on a partial surface if (for example, when) viewed from a plan view.
[0024] In one or more embodiments, the average particle size can be measured by methods well known to those skilled in the art, for example, by a particle size analyzer (e.g., HORIBA, LA-950 laser particle size analyzer), or by a transmission electron microscope (TEM) or a scanning electron microscope (SEM). In one or more embodiments, the average particle size value can be obtained by measuring using a dynamic light scattering method, performing data analysis, counting the number of particles in each particle size range, and calculating from the data. Unless otherwise specified, the average particle size (D 50 ) may mean the diameter of particles whose cumulative volume is 50% by volume in a particle size distribution. D50 refers to the average diameter (or size) of particles whose cumulative volume corresponds to 50 vol% in a particle size distribution (e.g., cumulative distribution), and refers to a value corresponding to 50% of the particle size starting from the smallest particle when the total number of particles is 100% in a distribution curve accumulated in the order of the smallest particle size to the largest particle size. In one or more embodiments, as used herein, if (e.g., when) no definition is provided in another manner, the average particle diameter (D50) is 50 ) refers to the diameter of particles of which the cumulative volume is 50% by volume in a particle size distribution obtained by randomly measuring the size (diameter or major axis length) of about 20 particles in a scanning electron microscope image. In the present disclosure, when the particles are spherical, "diameter" indicates the average particle diameter, and when the particles are non-spherical, "diameter" indicates the major axis length.
[0025] In this article, "or" is not interpreted as an exclusive meaning, for example, "A or B" is interpreted as including A, B, A+B, etc. Further, as used in this article, the term "and / or" includes any and all combinations of one or more related listed items. When before / after a list of elements, expressions such as "at least one of", "one of", and "selected from" modify the entire list of elements without modifying the individual elements of the list. For example, "at least one of a, b, and c", "selected from at least one of a, b, and c", "selected from at least one of a to c", etc. may indicate only a, only b, only c, both a and b (e.g., at the same time), both a and c (e.g., at the same time), both b and c (e.g., at the same time), all a, b, and c, or variations thereof. The " / " used in this article may be interpreted as "and" or "or" depending on the circumstances.
[0026] As used herein, the term "metal" is interpreted as a concept including ordinary metals, transition metals, and metalloids (semimetals).
[0027] Positive electrode active material
[0028] In one or more embodiments, the positive electrode active material includes a first positive electrode active material, a second positive electrode active material, and a third positive electrode active material, the first positive electrode active material includes a lithium nickel manganese type composite oxide having a nickel content (e.g., amount) greater than or equal to about 60 mol% based on 100 mol% of the total metals other than lithium included in the first positive electrode active material and is in the form of a plurality of secondary particles each including a plurality of aggregated primary particles (e.g., prepared by aggregating a plurality of primary particles), the second positive electrode active material is in the form of a plurality of individual particles (e.g., a plurality of individual particles each in the form of a whole particle) of a lithium nickel manganese type composite oxide having a nickel content (e.g., amount) greater than or equal to about 60 mol% based on 100 mol% of the total metals other than lithium included in the second positive electrode active material, and the third positive electrode active material is in the form of a plurality of particles including a lithium manganese type oxide.
[0029] Recently, since the price of rare metal cobalt has risen sharply, it is necessary and desirable to develop a positive electrode active material that excludes cobalt or includes a reduced amount of cobalt. Among these positive electrode active materials, positive electrode active materials with olivine crystal structures (such as lithium iron phosphate (LFP), lithium manganese phosphate (LMP), lithium manganese iron phosphate (LMFP), etc.) are limited in achieving high capacity due to the small amount of lithium available in the structure / low. Nickel-manganese positive electrode active materials with layered structures show excellent or appropriate capacity and efficiency characteristics due to the large amount of lithium available in the structure, so they can be applied to high-capacity batteries. However, since cobalt, which plays a key role in the layered structure, is excluded, the structural stability is deteriorated, and the resistance increases, resulting in the inability to ensure long-term cycle life characteristics. In addition, due to the exclusion of cobalt, the side reaction of the nickel-manganese positive electrode active material with the electrolyte can be accelerated under high voltage and high temperature conditions, resulting in the problem of increased gas generation and deterioration of cycle life characteristics.
[0030] In one or more embodiments of the present disclosure, a first positive electrode active material in the form of secondary particles which are particles comprising a lithium nickel manganese type composite oxide and a second positive electrode active material in the form of single particles are mixed with a third positive electrode active material (which is an inexpensive material) comprising a lithium manganese type oxide to propose a positive electrode active material that achieves long-term cycle life characteristics as well as high capacity and high energy density and exhibits improved high voltage performance.
[0031] The average particle size (D 50) may be larger than the average particle size (D 50 ). In the present disclosure, the first positive electrode active material may be described as large particles, and the second positive electrode active material may be described as small particles. The average particle size (D 50 ) may be larger than the average particle size (D 50 The average particle size of the third positive electrode active material (D 50 ) may be equal to or greater than the average particle size (D 50 ). For lithium nickel manganese based composite oxides, by appropriately or properly mixing large particles in the form of secondary particles and small particles in the form of single particles and additionally mixing lithium manganese based oxides, capacity and energy density can be maximized or increased and high voltage characteristics can be improved.
[0032] In one or more embodiments, the average particle size (D 50 ) means the diameter of particles accounting for 50% by volume of the cumulative volume in a particle size distribution obtained by randomly measuring the sizes (diameters or major axis lengths) of about 20 particles in a scanning electron microscope image.
[0033] In one or more embodiments, the average particle size (D 50 ) may be, for example, about 10 micrometers (μm) to about 20 μm, about 10 μm to about 18 μm, or about 12 μm to about 16 μm. The average particle size (D 50 ) may be, for example, about 0.5 μm to about 8 μm, about 1 μm to about 7 μm, about 1.5 μm to about 6 μm, or about 2 μm to about 5 μm. The average particle size (D 50 ) may be about 5 μm to about 12 μm, for example, about 6 μm to about 11 μm or about 7 μm to about 10 μm. If the average particle size of each positive electrode active material satisfies the above range, a relatively high capacity can be achieved and the energy density can be maximized or increased.
[0034] In one or more embodiments, based on the total weight of 100wt% of the first positive electrode active material, the second positive electrode active material, and the third positive electrode active material, the amount of the first positive electrode active material included may be about 60wt% to about 90wt%, the amount of the second positive electrode active material included may be about 5wt% to about 35wt%, and the amount of the third positive electrode active material included may be about 5wt% to about 35wt%. In some embodiments, based on the total weight of 100wt% of the first positive electrode active material, the second positive electrode active material, and the third positive electrode active material, the amount of the first positive electrode active material included may be about 60wt% to about 85wt%, the amount of the second positive electrode active material included may be about 10wt% to about 25wt%, and the amount of the third positive electrode active material included may be about 5wt% to about 20wt%. When the mixing ratio of each positive electrode active material satisfies the above range, the energy density can be further increased while increasing the capacity.
[0035] The lithium nickel manganese composite oxide of the first positive electrode active material and the lithium nickel manganese composite oxide of the second positive electrode active material may be the same or different from each other. In each lithium nickel manganese composite oxide, based on 100mol% of the total metal other than lithium in the lithium nickel manganese composite oxide, the nickel content (e.g., amount) may be greater than or equal to about 60mol%, such as about 60mol% to about 80mol%, about 65mol% to about 80mol%, about 70mol% to about 80mol%, about 60mol% to about 79mol%, about 60mol% to about 78mol% or about 60mol% to about 75mol%. When the nickel content (e.g., amount) satisfies the above range, even if the cobalt content (e.g., amount) is reduced, a relatively high capacity can be achieved and structural stability can be increased.
[0036] In one or more embodiments, based on 100 mol% of the total metal other than lithium in the lithium nickel manganese composite oxide, the manganese content (e.g., amount) may be, for example, about 10 mol% to about 40 mol%, such as about 10 mol% to about 39 mol%, about 10 mol% to about 35 mol%, about 10 mol% to about 30 mol%, about 10 mol% to about 29 mol%, about 15 mol% to about 39 mol%, about 20 mol% to about 39 mol%, or about 20 mol% to about 30%. When the manganese content (e.g., amount) satisfies the above range, the positive electrode active material can improve structural stability while achieving high capacity.
[0037] In one or more embodiments, in each of the first positive electrode active material and the second positive electrode active material, the corresponding lithium nickel manganese composite oxide may be a lithium nickel manganese aluminum composite oxide further including aluminum in addition to nickel and manganese. When the lithium nickel manganese composite oxide contains aluminum, it is beneficial to maintain a stable layered structure even if the cobalt element is excluded from the structure. Based on 100 mol% of the total metal other than lithium in the lithium nickel manganese aluminum composite oxide, the aluminum content (e.g., amount) may be greater than or equal to about 0.1 mol%, greater than or equal to about 0.5 mol%, or greater than or equal to about 1 mol%, for example, about 1 mol% to about 3 mol%, about 1 mol% to about 2.5 mol%, about 1 mol% to about 2 mol%, or about 1 mol% to about 1.9 mol%. If the aluminum content (e.g., amount) satisfies the above range, even if cobalt is excluded, a stable layered structure can be maintained, the problem of structural collapse caused by charging and discharging can be suppressed or reduced, and the long cycle life characteristics of the positive electrode active material can be achieved.
[0038] The lithium nickel manganese-based composite oxide of the first positive electrode active material and the lithium nickel manganese-based composite oxide of the second positive electrode active material may each be independently represented by Chemical Formula 1.
[0039] Chemical formula 1
[0040] Li a1 Ni x1 Mn y1 Al z1 M 1 w1 O 2-b1 X b1
[0041] In Chemical Formula 1, 0.9≤a1≤1.8, 0.6≤x1≤0.8, 0.1≤y1≤0.4, 0≤z1≤0.03, 0≤w1≤0.3, 0.9≤x1+y1+z1+w1≤1.1, and 0≤b1≤0.1, M 1 It may be one or more elements selected from boron (B), barium (Ba), calcium (Ca), cerium (Ce), chromium (Cr), iron (Fe), magnesium (Mg), molybdenum (Mo), niobium (Nb), silicon (Si), tin (Sn), strontium (Sr), titanium (Ti), vanadium (V), tungsten (W), yttrium (Y) and zirconium (Zr), and X may be one or more elements selected from fluorine (F), phosphorus (P) and sulfur (S).
[0042] In Chemical Formula 1, in some embodiments, 0.9 ≤ a1 ≤ 1.5, or 0.9 ≤ a1 ≤ 1.2. In one or more embodiments, the lithium nickel manganese composite oxide represented by Chemical Formula 1 may include aluminum, and in these embodiments, it may satisfy 0.6 ≤ x1 ≤ 0.8, 0.1 ≤ y1 ≤ 0.39, 0.01 ≤ z1 ≤ 0.03, and 0 ≤ w1 ≤ 0.29, for example, it may satisfy 0.6 ≤ x1 ≤ 0.8, 0.1 ≤ y1 ≤ 0.39, 0.01 < z1 ≤ 0.03, and 0 ≤ w1 ≤ 0.29.
[0043] In Chemical Formula 1, for example, in some embodiments, 0.6 ≤ x1 ≤ 0.79, 0.6 ≤ x1 ≤ 0.78, 0.6 ≤ x1 ≤ 0.75, 0.65 ≤ x1 ≤ 0.8, or 0.7 ≤ x1 ≤ 0.79; 0.1 ≤ y1 ≤ 0.35, 0.1 ≤ y1 ≤ 0.30, 0.1 ≤ y1 ≤ 0.29, 0.15 ≤ y1 ≤ 0.39, or 0.2 ≤ y1 ≤ 0.3; 0.01 ≤ z1 ≤ 0.025, 0.01 < z1 ≤ 0.02, or 0.01 < z1 ≤ 0.019; and 0 ≤ w1 ≤ 0.28, 0 ≤ w1 ≤ 0.27, 0 ≤ w1 ≤ 0.26, 0 ≤ w1 ≤ 0.25, 0 ≤ w1 ≤ 0.24, 0 ≤ w1 ≤ 0.23, 0 ≤ w1 ≤ 0.22, 0 ≤ w1 ≤ 0.21, 0 ≤ w1 ≤ 0.2, 0 ≤ w1 ≤ 0.15, 0 ≤ w1 ≤ 0.1, or 0 ≤ w1 ≤ 0.09.
[0044] In one or more embodiments, the lithium nickel manganese composite oxide may be a cobalt-free compound that does not include cobalt or includes a very small amount of cobalt. For example, in the lithium nickel manganese composite oxide of the first positive electrode active material and the lithium nickel manganese composite oxide of the second positive electrode active material, based on 100 mol% of the total metals other than lithium included in each corresponding lithium nickel manganese composite oxide, the cobalt content (e.g., amount) may each independently be about 0 mol% to about 0.01 mol%.
[0045] The first positive electrode active material
[0046] According to one or more embodiments, in the secondary particles that do not include the coating of the first positive electrode active material, the concentration of aluminum can be substantially uniform. For example, aluminum is uniformly (substantially uniformly) dispersed in the particles, there is no concentration gradient from the center of the particle to the surface direction in the particles, and there is no concentration difference between the inside and outside of the particles (e.g., between particles). This is a structure obtained by synthesizing nickel-manganese-aluminum hydroxide as a precursor and using the precursor to synthesize a composite oxide without additionally doping aluminum during the synthesis of the positive electrode active material. For example, in one or more embodiments, regardless of the position of each of the primary particles, the aluminum content (e.g., amount) inside each of the primary particles can be the same or similar. When a primary particle is selected from any position of a cross section of a secondary particle to measure the aluminum content (e.g., amount) not at the interface of the primary particle but inside the primary particle, the aluminum content (e.g., amount) can be the same / similar / substantially uniform regardless of the position of the primary particle (i.e., whether the primary particle is close to the center of the secondary particle or close to the surface of the secondary particle). In this structure, even if cobalt is absent or present in a very small amount, the layered structure can be stably maintained and neither aluminum byproducts nor aluminum aggregates are generated, while (e.g., simultaneously) improving the capacity, efficiency, and cycle life characteristics of the positive electrode active material.
[0047] The first positive electrode active material according to one or more embodiments may further include a coating layer on (e.g., arranged on) the surface of the secondary particles and comprising aluminum and zirconium. The first positive electrode active material including an aluminum-rich zirconium layer on the surface can effectively inhibit or reduce side reactions with the electrolyte at relatively high voltages, improving capacity and cycle life characteristics at relatively high voltages.
[0048] Based on 100 mol% of the total metal other than lithium in the first positive electrode active material, the aluminum content (e.g., amount) of the coating may be about 0.1 mol% to about 2 mol%. In some embodiments, based on 100 mol% of the total metal other than lithium in the first positive electrode active material, the aluminum content (e.g., amount) of the coating may be, for example, about 0.2 mol% to about 1.9 mol%, about 0.3 mol% to about 1.8 mol%, about 0.5 mol% to about 1.5 mol%, or about 0.8 mol% to about 1.3 mol%. The content of aluminum, etc. in the coating may be measured, for example, by SEM-EDS analysis of the surface or cross section of the positive electrode active material. When the aluminum content (e.g., amount) in the coating satisfies this range, the coating may have a substantially uniform and thin thickness, and may not increase the resistance of the positive electrode active material, and further, may effectively inhibit or reduce its side reaction with the electrolyte, thereby improving the cycle life characteristics of the rechargeable lithium battery at a relatively high voltage.
[0049] In one or more embodiments, based on 100 mol% of the total metal other than lithium in the first positive electrode active material, the zirconium content (e.g., amount) of the coating may be, for example, 0.05 mol% to about 1 mol%, about 0.1 mol% to about 1 mol%, about 0.1 mol% to about 0.9 mol%, about 0.1 mol% to about 0.8 mol%, or about 0.1 mol% to about 0.6 mol%. The content of zirconium and the like in the coating may be measured, for example, by SEM-EDS analysis of the surface or cross section of the positive electrode active material. When the zirconium content (e.g., amount) satisfies this range, a satisfactory coating may be formed on the positive electrode active material without deteriorating the capacity or increasing the resistance, which may effectively inhibit or reduce the side reaction with the electrolyte under relatively high voltage driving conditions, and further improve the capacity characteristics and cycle life characteristics.
[0050] In one or more embodiments, the coating of the first positive electrode active material may further include yttrium in addition to aluminum and zirconium, wherein the content (e.g., amount) of yttrium may be from about 0.05 mol% to about 1 mol%, from about 0.1 mol% to about 1 mol%, based on about 100 mol% of total metals other than lithium in the first positive electrode active material.
[0051] The coating of the first positive electrode active material may be formed as a film that continuously wraps the surface of each of the secondary particles (e.g., a shell that wraps the entire surface of each of the secondary particles). This is different from a structure in which the coating is coated on a portion of the surface of each of the secondary particles. According to one or more embodiments, because the coating is formed to completely cover the surface of each of the secondary particles but still has a very thin and substantially uniform thickness, the positive electrode active material may neither show an increase in resistance nor deteriorate capacity, but improve structural stability, effectively inhibit or reduce side reactions with the electrolyte, reduce gas generation, and achieve long-term cycle life characteristics.
[0052] In one or more embodiments, the thickness of the coating of the first positive electrode active material may be about 30 nanometers (nm) to about 500nm, for example, about 30nm to about 450nm, about 30nm to about 400nm, about 30nm to about 350nm, about 30nm to about 300nm, about 30nm to about 250nm, about 30nm to about 200nm, about 30nm to about 150nm, about 50nm to about 500nm, about 80nm to about 500nm or about 100nm to about 500nm. When the coating meets these thickness ranges, the structural stability of the positive electrode active material can be improved without increasing resistance and / or reducing capacity due to the coating, and the side reaction with the electrolyte can be effectively suppressed or reduced. The thickness of the coating can be measured by, for example, SEM, TEM, time-of-flight secondary ion mass spectrometry (TOF-SIMS), X-ray photoelectron spectroscopy (XPS) or energy dispersive spectroscopy (EDS) analysis, for example, by TEM-EDS line profile.
[0053] The coating of the first positive electrode active material has a thickness of tens to hundreds of nanometers, and therefore has a thin and substantially uniform thickness. For example, in one or more embodiments, the coating has a thickness deviation of less than or equal to about 20%, less than or equal to about 18%, or less than or equal to about 15% in a positive electrode active material particle. In this article, the thickness deviation of the coating refers to the deviation of the thickness of the coating in a positive electrode active material particle. The thickness deviation of the coating can be obtained, for example, by measuring the thickness of each of about 10 points of an electron microscope image of a cross section of a positive electrode active material particle, calculating its arithmetic mean, and then dividing the absolute value of the difference between a measured data and the arithmetic mean by the arithmetic mean and multiplying by 100. When the thickness deviation or standard deviation of the coating meets these ranges, on the surface of the positive electrode active material particle, the coating can be well formed into a film with a substantially uniform thickness, thereby improving the structural stability of the positive electrode active material, and effectively suppressing or reducing the side reaction with the electrolyte, and minimizing or reducing the resistance increase or capacity degradation caused by the coating.
[0054] In some embodiments, during the formation of the coating, aluminum may diffuse into the secondary particles. Accordingly, the positive electrode active material according to one or more embodiments may further include a grain boundary coating portion, which is located on the surface of each of the primary particles inside the secondary particles and contains aluminum. The interior of the secondary particle may refer to the entire interior portion except the surface of the secondary particle or may refer to a zone of about 60% of the radius of the secondary particle from the center of the secondary particle to the surface of the secondary particle (i.e., the distance from the surface of the secondary particle to the center of the secondary particle). The grain boundary coating portion is a different concept from the coating on the surface of the secondary particle, and refers to the coating portion on the surface of each of the primary particles inside the secondary particle. The presence of the grain boundary coating portion can be checked and confirmed by SEM-EDS analysis of the cross section of the positive electrode active material, etc. When the aluminum grain boundary coating portion is formed, the positive electrode active material can be further structurally stable and the cycle life characteristics can be improved.
[0055] The aluminum content (eg, amount) in the grain boundary coating portion is not particularly limited, but, for example, may be smaller than the aluminum content (eg, amount) in the coating layer.
[0056] On the other hand, in one or more embodiments, the aluminum content (e.g., amount) of the coating of the first positive electrode active material may be greater than the aluminum content (e.g., amount) of the coating of the second positive electrode active material, which will be described in more detail later. For example, in one or more embodiments, the aluminum content (e.g., amount) of the coating of the first positive electrode active material and the aluminum content (e.g., amount) of the coating of the second positive electrode active material may have a ratio of about 5:1 to about 2:1 or about 4:1 to about 2:1. In this article, the aluminum in the coating of the first positive electrode active material and the coating of the second positive electrode active material may not act as a resistor, but may maximize or increase capacity and cycle life characteristics and improve the structural stability of each.
[0057] Second positive electrode active material
[0058] The second positive electrode active material is in the form of a single particle (i.e., in the form of a single particle), the single particle exists alone without a grain boundary within the particle, is composed of one particle, and has a single particle, a monolithic structure, an integral structure or a non-aggregated particle in which the particles are not aggregated with each other in morphology but exist as independent phases, and can be expressed as a single particle (integral particle, single grain), such as a single crystal.
[0059] In one or more embodiments, the second positive electrode active material may further include a coating layer including aluminum and disposed on (eg, disposed on) the surface of the single particle. In these embodiments, the initial discharge capacity and cycle life characteristics of the positive electrode active material at a relatively high voltage may be improved.
[0060] In the coating of the second positive electrode active material, the aluminum content (e.g., amount) may be about 0.1 mol% to about 2 mol%, such as about 0.2 mol% to about 1.9 mol%, about 0.3 mol% to about 1.8 mol%, about 0.5 mol% to about 1.5 mol%, or about 0.8 mol% to about 1.3 mol%, based on 100 mol% of the total metals other than lithium in the second positive electrode active material. This refers only to the content (e.g., amount) of aluminum included in the coating of the second positive electrode active material, and does not include the content (e.g., amount) of aluminum included in a single particle. The aluminum content (e.g., amount) in the coating can be measured, for example, by SEM-EDS analysis of the surface or cross section of the positive electrode active material. If (for example, when) the aluminum content (for example, amount) in the coating layer of the second positive electrode active material satisfies these ranges (when), the coating layer may have a substantially uniform and thin thickness, which may not increase the resistance of the positive electrode active material, and effectively suppress or reduce the side reaction with the electrolyte, thereby improving the cycle life characteristics of the rechargeable lithium battery under relatively high voltage and relatively high temperature conditions. For example, if (for example, when) the aluminum content (for example, amount) of the coating layer of the second positive electrode active material is too much, the coating layer may not be substantially uniform, or the resistance may increase, thereby deteriorating the charge and discharge efficiency and the cycle life characteristics, but if (for example, when) the aluminum content (for example, amount) of the coating layer of the second positive electrode active material is too little, the coating layer may not have a suitable or appropriate thickness, thereby deteriorating the effect of suppressing or reducing the side reaction with the electrolyte.
[0061] In one or more embodiments, the coating of the second positive electrode active material may further include yttrium, which can further inhibit or reduce the side reaction of the positive electrode active material with the electrolyte solution at high voltage, thereby improving the cycle life characteristics. Based on 100 mol% of the total metal other than lithium in the second positive electrode active material, the yttrium content (e.g., amount) in the coating of the second positive electrode active material may be about 0.1 mol% to about 1 mol%, such as about 0.1 mol% to about 0.9 mol%, about 0.1 mol% to about 0.8 mol%, about 0.1 mol% to about 0.6 mol%, about 0.1 mol% to about 0.4 mol% or about 0.1 mol% to about 0.3 mol%. When the yttrium content (e.g., amount) meets these ranges, a satisfactory coating can be formed on the second positive electrode active material without deteriorating the capacity or increasing the resistance, thereby effectively inhibiting or reducing the side reaction with the electrolyte, and effectively reducing the amount of gas generated under high voltage or high temperature conditions.
[0062] The coating of the second positive electrode active material may be in the form of a film that continuously surrounds the surface of a single particle (e.g., the surface of each single particle), or, for example, may be in the form of a shell that surrounds the entire surface of a single particle (e.g., the entire surface of each single particle). This is different from a structure in which only a portion of the particle surface is partially coated. The coating according to one or more embodiments may be formed to have a very thin and substantially uniform thickness and completely cover the surface of a single particle, which neither increases the resistance of the positive electrode active material nor degrades the capacity, but exhibits improved structural stability, and can effectively inhibit or reduce side reactions with the electrolyte, thereby achieving long cycle life characteristics at high voltage.
[0063] In one or more embodiments, the thickness of the coating of the second positive electrode active material may be about 30nm to about 500nm, such as about 30nm to about 450nm, about 30nm to about 400nm, about 30nm to about 350nm, about 30nm to about 300nm, about 30nm to about 250nm, about 30nm to about 200nm, about 30nm to about 150nm, about 50nm to about 500nm, about 80nm to about 500nm or about 100nm to about 500nm. When the coating of the second positive electrode active material meets these thickness ranges, the structural stability of the positive electrode active material can be improved without increasing resistance and / or reducing capacity due to the coating, and side reactions with the electrolyte can be effectively suppressed or reduced. The thickness of the coating can be measured by, for example, SEM, TEM, TOF-SIMS, XPS or EDS analysis, for example, it can be measured by TEM-EDS line profile.
[0064] The coating of the second positive electrode active material has a thin and substantially uniform thickness of tens to hundreds of nanometers. For example, in one or more embodiments, within a positive electrode active material particle (e.g., a single particle), the coating may have a thickness deviation of less than or equal to about 20%, less than or equal to about 18%, or less than or equal to about 15%. In this article, the thickness deviation of the coating refers to the deviation of the thickness of the coating on a positive electrode active material particle. The thickness deviation of the coating can be calculated, for example, by measuring the thickness of each of about 10 points of an electron microscope image of a cross-section of a positive electrode active material particle, calculating its arithmetic mean, and then dividing the absolute value of the difference between a measured data and the arithmetic mean by the arithmetic mean and multiplying by 100. When the coating has a thickness deviation or standard deviation within these ranges, a coating with a substantially uniform thickness is well formed on the surface of the positive electrode active material particle, which can improve the structural stability of the positive electrode active material, effectively inhibit or reduce side reactions with the electrolyte, and minimize or reduce the increase in resistance or capacity degradation.
[0065] In the coating layer of the second positive electrode active material, aluminum may exist in the form of a continuous film (eg, a substantially continuous film) and yttrium may exist in the form of islands (eg, individual islands) due to the characteristics of each element.
[0066] In one or more embodiments, aluminum and yttrium may be mixed within a coating, but the aluminum may still be present as a continuous (eg, substantially continuous) layer and the yttrium may be present as islands, but embodiments of the present disclosure are not limited to these forms.
[0067] In one or more embodiments, aluminum and yttrium may form (or provide) separate layers. For example, in one or more embodiments, the second positive electrode active material may include: a first coating layer on (e.g., arranged on) the surface of a single particle and comprising aluminum, and a second coating layer on (e.g., arranged on) the first coating layer and comprising yttrium. A first coating layer in the form of a thin film may be formed when aluminum is first attached or adsorbed on the surface of a single particle, and then yttrium may be coated thereon to form (or provide) a second coating layer. Of course, in some embodiments, aluminum and yttrium may be mixed in the first coating layer and the second coating layer, but the first coating layer may be an aluminum-rich coating layer consisting mainly of aluminum, and the second coating layer may be a yttrium-rich coating layer consisting mainly of yttrium. In these embodiments, yttrium may exist in the second coating layer in the form of islands, but is not particularly limited.
[0068] In one or more embodiments, the thickness of the first coating and the second coating is not particularly limited. However, the thickness of the first coating may be about 10nm to about 200nm, such as about 20nm to about 200nm, about 30nm to about 200nm, or about 30nm to about 180nm. The thickness of the second coating may be about 20nm to about 300nm, such as about 20nm to about 250nm, about 20nm to about 200nm, about 30nm to about 300nm, or about 50nm to about 300nm. When each of the thickness of the first coating and the thickness of the second coating meets the above range, the structural stability of the positive electrode active material can be improved, the resistance will not be increased and / or the capacity will not be reduced due to the coating, and the cycle life characteristics at relatively high voltages can be improved by effectively suppressing or reducing the side reactions with the electrolyte.
[0069] The third positive electrode active material
[0070] The third positive electrode active material may be in the form of a single particle or a plurality of secondary particles each including a plurality of primary particles aggregated (eg, prepared by aggregating a plurality of primary particles).
[0071] The third positive electrode active material, the lithium manganese-based oxide, may be, for example, a LiMn 2 O 4Spinel-structured lithium manganese oxides as a basic component. In one or more embodiments, in addition to manganese, the lithium manganese oxides may further include, for example, aluminum, magnesium, yttrium, and / or any suitable combination thereof, and may not include (e.g., may exclude) cobalt or may include a very small amount of cobalt.
[0072] For example, in one or more embodiments, the lithium manganese oxides of the third positive electrode active material may be represented by Chemical Formula 3.
[0073] Chemical Formula 3
[0074] Li a3 Mn x3 M 3 y3 O 4-b3 X b3
[0075] In Chemical Formula 3, 0.9 ≤ a3 ≤ 1.8, 1.7 ≤ x3 ≤ 2, 0 ≤ y3 ≤ 0.3, 1.9 ≤ x3 + y3 ≤ 2.1, and 0 ≤ b3 ≤ 0.1, M 3 may be one or more elements selected from Al, B, Ba, Ca, Ce, Cr, Fe, Mg, Mo, Nb, Si, Sn, Sr, Ti, V, W, Y, and Zr, and X may be one or more elements selected from F, P, and S.
[0076] In Chemical Formula 3, in one or more embodiments, 1.8 ≤ x3 ≤ 2, 0 ≤ y3 ≤ 0.2; 1.9 ≤ x3 ≤ 2, 0 ≤ y3 ≤ 0.1; or 1.7 ≤ x3 < 2, 0 < y3 ≤ 0.3.
[0077] In one or more embodiments, the lithium manganese oxides of the third positive electrode active material may be represented by Chemical Formula 4.
[0078] Chemical Formula 4
[0079] Li a4 Mn x4 Al y4 Mg z4 M 4 w4 O 4-b4 X b4
[0080] In Chemical Formula 4, 0.9 ≤ a4 ≤ 1.8, 1.7 ≤ x4 < 2.0, 0 < y4 ≤ 0.015, 0 < z4 ≤ 0.010, 0 ≤ w4 < 0.3, 1.9 ≤ x4 + y4 + z4 + w4 ≤ 2.1, and 0 ≤ b4 ≤ 0.1, M 4It may be one or more elements selected from B, Ba, Ca, Ce, Cr, Fe, Mo, Nb, Si, Sn, Sr, Ti, V, W, Y and Zr, and X may be one or more elements selected from F, P and S.
[0081] In one or more embodiments, Al may be included in an amount of about 0 mol% to about 1.5 mol%, about 0.01 mol% to about 1.0 mol%, or about 0.1 mol% to about 0.8 mol%, and Mg may be included in an amount of about 0 mol% to about 1.0 mol%, about 0.01 mol% to about 0.9 mol%, or about 0.1 mol% to about 0.8 mol%, based on 100 mol% of total metals other than lithium in the lithium manganese-based oxide.
[0082] In one or more embodiments, the third positive electrode active material may further include a coating comprising aluminum on (e.g., arranged on) the surface of the particle. In this article, the side reaction of the positive electrode active material with the electrolyte at a relatively high voltage can be effectively suppressed or reduced, thereby improving the cycle life characteristics. In the third positive electrode active material, based on 100 mol% of the total metal other than lithium included in the third positive electrode active material, the coating may include about 0.01 mol% to about 1 mol% or, for example, about 0.05 mol% to about 0.5 mol% of aluminum.
[0083] In the positive electrode active material according to one or more embodiments, the content (e.g., amount) of cobalt may be, for example, less than or equal to about 0.01 mol%, less than or equal to about 0.005 mol%, less than or equal to about 0.001 mol%, or, for example, from about 0 mol% to about 0.01 mol%, based on about 100 mol% of metals other than lithium included in the positive electrode active material. According to one or more embodiments, the positive electrode active material may be, for example, a cobalt-free positive electrode active material.
[0084] In one or more embodiments, the positive electrode active material according to one or more embodiments may not include (e.g., may exclude) sodium. Generally speaking, sodium ions can be used in the process of preparing the positive electrode active material, but according to the preparation method described in more detail later, positive electrode active material particles having a stable structure and a coating layer having a substantially uniform thickness can be formed without using sodium ions.
[0085] Method for preparing positive electrode active material
[0086] In one or more embodiments, a method for preparing a positive electrode active material may include: (i) mixing and heat treating a nickel-manganese-based composite hydroxide having a nickel content (e.g., nickel amount) greater than or equal to about 60 mol% based on 100 mol% of the total metal of the nickel-manganese-based composite hydroxide with a lithium raw material to prepare a first positive electrode active material in the form of secondary particles, each of which is formed by agglomerating multiple primary particles, (ii) mixing and heat treating a nickel-manganese-based composite hydroxide having a nickel content (e.g., amount) greater than or equal to about 60 mol% based on 100 mol% of the total metal of the nickel-manganese-based composite hydroxide with a lithium raw material to prepare a second positive electrode active material in the form of a single particle, (iii) preparing a third positive electrode active material including a lithium manganese-based oxide, and (iv) mixing the first positive electrode active material, the second positive electrode active material, and the third positive electrode active material.
[0087] In the preparation process of each of the first positive electrode active material and the second positive electrode active material, the nickel-manganese composite hydroxide may not include (e.g., may exclude) cobalt or may include trace amounts of cobalt, for example, it may be a cobalt-free nickel-manganese composite hydroxide (e.g., a cobalt-free nickel-manganese-aluminum composite hydroxide). The nickel-manganese composite hydroxide may be prepared by a general coprecipitation method.
[0088] Based on 100mol% of the total metal in the nickel-manganese composite hydroxide, the nickel content (e.g., amount) in the nickel-manganese composite hydroxide may be greater than or equal to about 60mol%, such as about 60mol% to about 80mol%, about 65mol% to about 80mol%, about 70mol% to about 80mol%, about 60mol% to about 79mol%, about 60mol% to about 78mol% or about 60mol% to about 75mol%. If (e.g., when) the nickel content (e.g., amount) satisfies the above range (when), even if the cobalt content (e.g., amount) is reduced, relatively high capacity can be achieved, and structural stability can be increased.
[0089] The manganese content (e.g., the amount of manganese) in the nickel-manganese-based composite hydroxide may be about 10 mol% to about 40 mol%, about 10 mol% to about 39 mol%, about 10 mol% to about 35 mol%, about 10 mol% to about 30 mol%, about 10 mol% to about 29 mol%, about 15 mol% to about 39 mol%, about 20 mol% to about 39 mol%, or about 20 mol% to about 30 mol%, based on 100 mol% of total metals in the nickel-manganese-based composite hydroxide.
[0090] In one or more embodiments, if (for example, when) the nickel-manganese composite hydroxide further includes aluminum (when), based on 100mol% of the total metal in the nickel-manganese composite hydroxide, the aluminum content (for example, the amount of aluminum) may be greater than or equal to about 0.1mol%, greater than or equal to about 0.5mol%, or greater than or equal to about 1mol%, for example, about 1mol% to about 3mol%, about 1mol% to about 2.5mol%, about 1mol% to about 2mol%, or about 1mol% to about 1.9mol%. If (for example, when) the manganese content and aluminum content of the nickel-manganese composite hydroxide meet the above range (when), a relatively high capacity can be achieved, while the structural stability of the positive electrode active material can be increased, and the production price can be reduced to increase economic benefits.
[0091] In the nickel-manganese composite hydroxide, the cobalt content (e.g., amount) may be less than or equal to about 0.01 mol%, less than or equal to about 0.005 mol%, or less than or equal to about 0.001 mol%, based on 100 mol% of the total metal in the nickel-manganese composite hydroxide. The nickel-manganese composite hydroxide may be economical because it avoids the increase in unit cost caused by cobalt, maximizes capacity, and improves structural stability.
[0092] As an example, in one or more embodiments, the nickel-manganese-based composite hydroxide may be represented by Chemical Formula 2.
[0093] Chemical formula 2
[0094] Ni x2 Mn y2 Al z2 M 2 w2 (OH) 2
[0095] In Chemical Formula 2, 0.6≤x2≤0.8, 0.1≤y2≤0.4, 0≤z2≤0.03, 0≤w2≤0.3, and 0.9≤x2+y2+z2+w2≤1.1, and M 2 It may be one or more elements selected from B, Ba, Ca, Ce, Cr, Fe, Mg, Mo, Nb, Si, Sn, Sr, Ti, V, W, Y and Zr.
[0096] In Chemical Formula 2, for example, in some embodiments, 0.6≤x2≤0.8, 0.1≤y2≤0.39, 0.01≤z2≤0.03, and 0≤w2≤0.29.
[0097] In one or more embodiments, in the preparation of the first positive electrode active material, aluminum is not additionally doped, but an aluminum raw material can be used to prepare a precursor, so that a nickel-manganese-aluminum composite hydroxide in which aluminum is uniformly (substantially uniformly) dispersed in the structure can be used as a precursor. When such a precursor is used, the positive electrode active material can stably maintain a layered structure despite repeated charging and discharging without cobalt, and aluminum byproducts or aluminum aggregates may not be formed, thereby improving the capacity and efficiency characteristics and cycle life characteristics of the positive electrode active material.
[0098] In one or more embodiments, in the preparation of the first positive electrode active material, the nickel manganese composite hydroxide and the lithium raw material can be mixed in a molar ratio of about 1:0.9 to about 1:1.8 (e.g., about 1:0.9 to about 1:1.5 or about 1:0.9 to about 1:1.2). After mixing, a preliminary heat treatment of about 2 hours to about 20 hours or about 4 hours to about 12 hours can be performed under an oxygen atmosphere, for example, at about 750°C to about 950°C, about 780°C to about 900°C, or about 810°C to about 890°C. By preliminary heat treatment, a lithium nickel manganese composite oxide can be obtained. Based on about 100 mol% of the total metal in the lithium nickel manganese composite oxide, the obtained lithium nickel manganese composite oxide may include nickel in an amount of about 60 mol% or more, for example, about 60 mol% to about 80 mol%, but does not contain cobalt or includes a very small amount of cobalt less than or equal to about 0.01 mol%.
[0099] The method for preparing a positive electrode active material according to one or more embodiments may further include a coating process after obtaining a lithium nickel manganese composite oxide during the preparation of the first positive electrode active material. The lithium nickel manganese composite oxide has a residual lithium content (e.g., amount) and different surface characteristics significantly different from oxides having other compositions (e.g., conventional nickel oxides such as lithium nickel cobalt manganese composite oxides or lithium nickel cobalt aluminum composite oxides, etc.), and the conventional coating methods used in the art cannot successfully form (or provide) a good or appropriate coating in the form of a substantially uniform film thereon. One or more embodiments of the present disclosure provide a method for improving high voltage characteristics by forming (or providing) a coating having a substantially uniform and very thin thickness on the surface of a lithium nickel manganese composite oxide having a very small cobalt content (e.g., amount) and a nickel content (e.g., amount) of about 60 mol% or more. For example, after adding an aluminum raw material to an aqueous solvent, a lithium nickel manganese composite oxide is added thereto, and then mixed, dried and reheated to form (or provide) a coating according to one or more embodiments. This may be a wet coating method.
[0100] The aqueous solvent may include distilled water, an alcohol solvent and / or (e.g., any appropriate) combination thereof. The aluminum raw material may include, for example, aluminum nitrate, aluminum sulfate, aluminum carbonate, aluminum hydroxide and / or (e.g., any appropriate) combination thereof. For example, in one or more embodiments, the aluminum raw material may include aluminum sulfate, and in these embodiments, it is advantageous to form (or provide) a coating having a substantially uniform thickness on the surface of the lithium nickel manganese composite oxide particles. Based on 100 mol% of the total metal other than lithium in the first positive electrode active material, the aluminum content (e.g., amount) in the aluminum raw material may be designed to be about 0.1 mol% to about 2 mol%, such as about 0.2 mol% to about 1.9 mol%, about 0.3 mol% to about 1.8 mol%, about 0.5 mol% to about 1.5 mol% or about 0.8 mol% to about 1.3 mol%.
[0101] The solution in which the aluminum raw material is mixed in the aqueous solvent may have a pH of about 1.5 to about 3.5 (e.g., about 2.0 to about 3.4, about 2.5 to about 3.3, about 2.7 to about 3.3, or about 2.9 to about 3.2). The mixing and stirring of the lithium nickel manganese composite oxide and the aqueous solvent (in which the aluminum raw material is mixed) can be carried out for about 5 minutes to about 80 minutes, about 5 minutes to about 60 minutes, or about 5 minutes to about 40 minutes. After stirring, the mixed solution may have a pH of about 4.5 to about 8.5, (e.g., about 5.0 to about 8.0, about 5.5 to about 7.5, or about 6.0 to about 7.0). When these conditions are met, it is beneficial to form (or provide) a coating having a substantially uniform thickness.
[0102] The drying after the mixing process may be understood as a process of removing the solvent, and may be performed, for example, at about 40° C. to about 240° C., about 100° C. to about 220° C., or about 150° C. to about 200° C. The reheating treatment may be understood as a process of forming (or providing) a coating on the surface of the lithium nickel manganese-based oxide particles, for example, in an oxygen atmosphere at a temperature range of about 700° C. to about 850° C., about 750° C. to about 840° C., or about 800° C. to about 830° C. for about 2 to about 20 hours or about 3 to about 10 hours.
[0103] In order to coat zirconium and aluminum, after adding a zirconium raw material to the product obtained after drying, a reheating treatment may be performed. The zirconium raw material may be, for example, zirconium oxide, and zirconium oxide may be added to a zirconium content (e.g., amount) of about 0.05 mol% to about 1 mol% based on about 100 mol% of the total metals other than lithium in the first positive electrode active material.
[0104] In the preparation of the second positive electrode active material, the nickel manganese composite hydroxide and the lithium raw material can be mixed in a molar ratio of about 1:0.9 to about 1:1.8 (e.g., about 1:0.9 to about 1:1.5 or about 1:0.9 to about 1:1.2). After mixing, a preliminary heat treatment of about 2 hours to about 20 hours or about 4 hours to about 12 hours can be performed under an oxygen atmosphere, for example, at about 750°C to about 950°C, about 780°C to about 900°C, or about 810°C to about 890°C. By preliminary heat treatment, a lithium nickel manganese composite oxide can be obtained. Based on about 100 mol% of the total metal in the obtained lithium nickel manganese composite oxide, the obtained lithium nickel manganese composite oxide may include nickel in an amount of about 60 mol% or more, for example, about 60 mol% to about 80 mol%, but does not include cobalt or includes a very small amount of cobalt of about 0.01 mol% or less. In one or more embodiments, the method may further include pulverizing to obtain a lithium nickel manganese composite oxide in the form of a single particle.
[0105] In one or more embodiments, in the preparation of the second positive electrode active material, after obtaining a single particle containing a lithium nickel manganese composite oxide by mixing a nickel manganese composite hydroxide and a lithium raw material and preliminarily heat treating the nickel manganese composite hydroxide and the lithium raw material, a coating process of the single particle may be further included. The second positive electrode active material in the form of a single particle coated with aluminum may not be achieved by conventional coating methods in the art, but, instead, a wet coating method according to one or more embodiments of the present disclosure can be used to form (or provide) a satisfactory coating as a substantially uniform film. For example, after mixing the aluminum raw material into an aqueous solvent, a lithium nickel manganese composite oxide in the form of a single particle is added thereto, and then mixed, dried, and reheated to prepare a second positive electrode active material.
[0106] The details about the aqueous solvent and the aluminum raw material may be independently the same as described above. Based on 100 mol% of the total metal other than lithium in the second positive electrode active material, the aluminum content (e.g., amount) in the aluminum raw material may be designed to be in the range of about 0.1 mol% to about 2 mol% (e.g., about 0.2 mol% to about 1.9 mol%, about 0.3 mol% to about 1.8 mol%, about 0.5 mol% to about 1.5 mol% or about 0.8 mol% to about 1.3 mol%).
[0107] When the aluminum raw material is added to the aqueous solvent, the yttrium raw material may also be added together to coat Al and Y. The yttrium raw material may be, for example, yttrium nitrate, yttrium sulfate, yttrium carbonate, yttrium hydroxide and / or (for example, any appropriate) combination thereof. In the yttrium raw material, based on about 100 mol% of the total metal other than lithium in the second positive electrode active material, the yttrium content (for example, amount) may be designed to be about 0.1 mol% to about 1 mol%, for example, about 0.1 mol% to about 0.9 mol%, about 0.1 mol% to about 0.8 mol%, about 0.1 mol% to about 0.6 mol%, about 0.1 mol% to about 0.4 mol% or about 0.1 mol% to about 0.3 mol%. If the content of the coating raw material is designed to have these ranges, the coating may be formed to have a thin and substantially uniform thickness of tens of nanometers to hundreds of nanometers, which may reduce the amount of gas generated by the rechargeable lithium battery under high voltage conditions, and improve high capacity and long cycle life characteristics.
[0108] The solution obtained by mixing the aluminum raw material and the optional yttrium raw material in an aqueous solvent may have a pH of about 1.5 to about 3.5 (e.g., about 2.0 to about 3.4, about 2.5 to about 3.3, about 2.7 to about 3.3, or about 2.9 to about 3.2). The mixing and stirring of the lithium nickel manganese composite oxide and the aqueous solvent (in which the aluminum raw material and the yttrium raw material are mixed) can be carried out for about 5 minutes to about 80 minutes, about 5 minutes to about 60 minutes, or about 5 minutes to about 40 minutes. After stirring, the mixed solution may have a pH of about 4.5 to about 8.5 (e.g., about 5.0 to about 8.0, about 5.5 to about 7.5, or about 6.0 to about 7.0). When these conditions are met, it is beneficial to form (or provide) a coating having a substantially uniform thickness.
[0109] Drying after the mixing process can be understood as a process for removing the solvent, and can be performed, for example, at about 40°C to about 240°C, about 100°C to about 220°C, or about 150°C to about 200°C. Reheating treatment can be understood as a process for forming (or providing) a coating on the surface of lithium nickel manganese composite oxide particles, for example, in an oxygen atmosphere at a temperature range of about 700°C to about 850°C, about 750°C to about 840°C, or about 800°C to about 830°C for about 2 hours to about 20 hours or about 3 hours to about 10 hours. In one or more embodiments, the reheating treatment temperature can be lower than the previous / previous heat treatment temperature, and the reheating treatment time can be the same as or shorter than the previous / previous heat treatment time. Under these conditions, reheating treatment can be performed to obtain a desired or appropriate coating.
[0110] Based on the total amount of about 100wt% of the first positive electrode active material, the second positive electrode active material and the third positive electrode active material, the mixing of the first positive electrode active material, the second positive electrode active material and the third positive electrode active material can utilize about 60wt% to about 90wt% of the first positive electrode active material, about 5wt% to about 35wt% of the second positive electrode active material and about 5wt% to about 35wt% of the third positive electrode active material. Non-limiting examples of the positive electrode active material obtained by mixing may include about 60wt% to about 85wt% of the first positive electrode active material, about 10wt% to about 25wt% of the second positive electrode active material and about 5wt% to about 20wt% of the third positive electrode active material. When each of the positive electrode active materials is mixed according to these proportions, the capacity can be increased and the energy density can also be maximized or increased.
[0111] Positive electrode
[0112] In one or more embodiments, the positive electrode may include a positive electrode current collector and a positive electrode active material layer on the positive electrode current collector, wherein the positive electrode active material layer includes the positive electrode active material described above. In some embodiments, in addition to the aforementioned positive electrode active material, the positive electrode active material layer may further include other types (kinds) of positive electrode active materials. In one or more embodiments, the positive electrode active material layer may optionally further include a binder, a conductive material and / or a combination thereof (e.g., any appropriate).
[0113] According to one or more embodiments, the loading level of the positive electrode active material layer may be about 10 mg / cm 2 ~ about 40mg / cm 2 , for example about 10 mg / cm 2 ~about 30mg / cm 2 or about 10 mg / cm 2 ~about 20mg / cm 2 . In one or more embodiments, the density of the positive electrode active material layer in the final pressed positive electrode (e.g., positive electrode) may be about 3.5 g / cc to about 3.7 g / cc, such as about 3.5 g / cc to about 3.6 g / cc or about 3.5 g / cc to about 3.58 g / cc. When the positive electrode active material according to one or more embodiments is applied, the implementation of the load level and density of such a positive electrode active material layer is facilitated, and the positive electrode satisfying the load level and density of the positive electrode active material layer within the above range is suitable for implementing a high-capacity, high-energy-density rechargeable lithium battery.
[0114] Binder
[0115] The binder improves the bonding properties between the positive electrode active material particles and between the positive electrode active material particles and the positive electrode current collector. Examples of the binder may include polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene oxide-containing polymers, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, (meth) acrylated styrene-butadiene rubber, epoxy resin, (meth) acrylic resin, polyester resin and nylon, but the embodiments of the present disclosure are not limited thereto.
[0116] Conductive Materials
[0117] A conductive material (e.g., an electronic conductor) may be included to provide electrode conductivity, and any conductive material may be used as the conductive material unless it causes a chemical change. Non-limiting examples of conductive materials may include: carbon-based materials such as natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, carbon nanofiber, carbon nanotube, etc.; metal-based materials including metal powders or metal fibers of copper, nickel, aluminum, silver, etc.; conductive polymers such as polyphenylene derivatives; and / or (e.g., any appropriate) mixtures thereof.
[0118] Each content (eg, amount) of the binder and the conductive material may be about 0.5 wt % to about 5 wt % or about 0.5 wt % to about 3 wt % based on 100 wt % of the positive electrode active material layer.
[0119] The positive electrode current collector may include an Al foil, but embodiments of the present disclosure are not limited thereto.
[0120] Rechargeable lithium battery
[0121] According to one or more embodiments of the present disclosure, a rechargeable lithium battery may include the aforementioned positive electrode, negative electrode, and electrolyte.
[0122] Rechargeable lithium batteries may be classified into cylindrical batteries, prismatic batteries, pouch-type batteries, coin-type batteries, etc. according to their shapes. Figure 1 Schematically illustrates a cross-sectional view of a rechargeable lithium battery according to one or more embodiments. Figure 1 , the rechargeable lithium battery 100 may include an electrode assembly 40 having a separator 30 interposed between a positive electrode 10 and a negative electrode 20, and a case 50 accommodated in the case 50. The positive electrode 10, the negative electrode 20, and the separator 30 may be impregnated with an electrolyte (not shown).
[0123] The rechargeable lithium battery according to one or more embodiments can be rechargeable at a relatively high voltage or can be adapted to be driven at a relatively high voltage. For example, in one or more embodiments, the charging voltage of the rechargeable lithium battery can be about 4.3V to about 4.6V or about 4.40V to about 4.55V. By applying the positive electrode active material according to one or more embodiments, even when charging at a relatively high voltage (for example, when), the rechargeable lithium battery can significantly reduce the amount of generated gas, and can also achieve relatively high capacity and long cycle life characteristics.
[0124] Negative electrode
[0125] The negative electrode may include a negative electrode current collector and a negative electrode active material layer on the negative electrode current collector, and the negative electrode active material layer may include a negative electrode active material, a binder, a conductive material, and / or a combination thereof (for example, any suitable combination).
[0126] Negative electrode active material
[0127] The negative electrode active material may include a material that reversibly intercalates / deintercalates lithium ions, lithium metal, a lithium metal alloy, a material capable of doping / dedoping lithium, or a transition metal oxide.
[0128] The material that reversibly intercalates / deintercalates lithium ions may include, for example, crystalline carbon, amorphous carbon, and / or a combination thereof (for example, any suitable combination) as a carbon-based negative electrode active material. The crystalline carbon may be amorphous, or natural graphite or artificial graphite in the form of flakes, platelets, spheres, or fibers (for example, in fiber form). The amorphous carbon may be soft carbon, hard carbon, mesophase pitch carbonization product, calcined coke, etc.
[0129] The lithium metal alloy includes an alloy of lithium and a metal selected from sodium (Na), potassium (K), rubidium (Rb), cesium (Cs), francium (Fr), beryllium (Be), magnesium (Mg), calcium (Ca), strontium (Sr), silicon (Si), antimony (Sb), lead (Pb), indium (In), zinc (Zn), barium (Ba), radium (Ra), germanium (Ge), aluminum (Al), and tin (Sn).
[0130] The material capable of doping / dedoping lithium may be a Si-based negative electrode active material or a Sn-based negative electrode active material. The Si-based negative electrode active material may include silicon, a silicon-carbon composite, SiO x (0 < x ≤ 2), a Si-Q alloy (where Q is an element selected from alkali metals, alkaline earth metals, group 13 elements, group 14 elements (excluding Si), group 15 elements, group 16 elements, transition metals, rare earth elements, and / or a combination thereof (for example, any suitable combination), for example, magnesium (Mg), calcium (Ca), strontium (Sr), barium (Ba), radium (Ra), scandium (Sc), yttrium (Y), titanium (Ti), zirconium (Zr), hafnium (Hf), (Rf), vanadium (V), niobium (Nb), tantalum (Ta), dubnium (Db), chromium (Cr), molybdenum (Mo), tungsten (W), (Sg), technetium (Tc), rhenium (Re), (Bh), iron (Fe), lead (Pb), ruthenium (Ru), osmium (Os), (Hs), rhodium (Rh), iridium (Ir), palladium (Pd), platinum (Pt), copper (Cu), silver (Ag), gold (Au), zinc (Zn), cadmium (Cd), boron (B), aluminum (Al), gallium (Ga), tin (Sn), indium (In), thallium (Tl), germanium (Ge), phosphorus (P), arsenic (As), antimony (Sb), bismuth (Bi), sulfur (S), selenium (Se), tellurium (Te), polonium (Po) and / or its (e.g., any suitable) combination) and / or its (e.g., any suitable) combination. The Sn-based negative electrode active material can be Sn, SnO k (0 < k ≤ 2) (e.g., SnO 2 ), Sn alloy and / or its (e.g., any suitable) combination.
[0131] The silicon-carbon composite can be a composite of silicon and amorphous carbon in particulate form. The average particle size (D 50 ) of the silicon-carbon composite particles (e.g., secondary particles) can be, for example, about 0.5 micrometers (μm) to about 20 μm. According to one or more embodiments, the silicon-carbon composite can be in the form of silicon particles and amorphous carbon coated on the surface of each of the silicon particles. For example, in some embodiments, the silicon-carbon composite can include secondary particles (cores) in which silicon primary particles are assembled and an amorphous carbon coating (shell) on the surface of the secondary particles. Amorphous carbon can also be present between the silicon primary particles, for example, each of the silicon primary particles can be coated with amorphous carbon. The secondary particles can be present dispersed in an amorphous carbon matrix.
[0132] The silicon-carbon composite can further include crystalline carbon. For example, in one or more embodiments, the silicon-carbon composite can include: a core (e.g., primary particles) including crystalline carbon and silicon particles (e.g., primary particles) and an amorphous carbon coating on the surface of the core. The crystalline carbon can be artificial graphite, natural graphite, and / or its (e.g., any suitable) combination. The amorphous carbon can include soft carbon, hard carbon, mesophase pitch carbonized product, or calcined coke.
[0133] When the silicon-carbon composite includes silicon and amorphous carbon, based on 100 wt% of the total weight of the silicon-carbon composite, the content (e.g., amount) of silicon can be about 10 wt% to about 50 wt% and the content (e.g., amount) of amorphous carbon can be about 50 wt% to about 90 wt%. In one or more embodiments, if (e.g., when) the silicon-carbon composite includes silicon, amorphous carbon, and crystalline carbon, then based on 100 wt% of the total weight of the silicon-carbon composite, the content (e.g., amount) of silicon can be about 10 wt% to about 50 wt%, the content (e.g., amount) of crystalline carbon can be about 10 wt% to about 70 wt%, and the content (e.g., amount) of amorphous carbon can be about 20 wt% to about 40 wt%.
[0134] In one or more embodiments, the thickness of the amorphous carbon coating can be about 5 nm to about 100 nm. The average particle diameter (D 50 ) of the silicon particles (primary particles) can be about 10 nm to about 1 μm or about 10 nm to about 200 nm. The silicon particles can exist as silicon alone, in the form of a silicon alloy, or in an oxidized form of silicon. The oxidized form of silicon can be represented by SiO x (0 < x ≤ 2). In one or more embodiments, the atomic content (e.g., amount) ratio Si:O indicating the degree of oxidation can be about 99:1 to about 33:67. As used herein, if (e.g., when) no other definition is provided, the average particle diameter (D 50 ) indicates the diameter of the particles in which the cumulative volume in the particle size distribution is about 50 vol%.
[0135] In one or more embodiments, Si-based negative electrode active materials or Sn-based negative electrode active materials can be mixed with carbon-based negative electrode active materials. When mixing and using Si-based negative electrode active materials or Sn-based negative electrode active materials and carbon-based negative electrode active materials, the mixing ratio can be a weight ratio of about 1:99 to about 90:10.
[0136] Binder
[0137] The binder is used to bond the negative electrode active material particles to each other well and is also used to bond the negative electrode active material to the negative electrode current collector. The binder can be a non-aqueous (e.g., water-insoluble) binder, an aqueous (water-soluble) binder, a dry binder, and / or a combination thereof (e.g., any suitable combination).
[0138] The non-aqueous binder can include polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene-propylene copolymer, polystyrene, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, polyamideimide, polyimide, and / or a combination thereof (e.g., any suitable combination).
[0139] The aqueous binder may include styrene-butadiene rubber, (meth)acrylated styrene-butadiene rubber, (meth)acrylonitrile-butadiene rubber, (meth)acrylic rubber, butyl rubber, fluororubber, polyethylene oxide, polyvinyl pyrrolidone, polyepichlorohydrin, polyphosphazene, poly(meth)acrylonitrile, ethylene propylene diene copolymer, polyvinyl pyridine, chlorosulfonated polyethylene, latex, polyester resin, (meth)acrylic resin, phenol resin, epoxy resin, polyvinyl alcohol and / or (e.g., any suitable) combination thereof.
[0140] If (for example, when) an aqueous binder is used as a binder in the negative electrode active material layer, a cellulose compound capable of imparting viscosity may be further included. As the cellulose compound, one or more of carboxymethyl cellulose, hydroxypropyl methyl cellulose, methyl cellulose and an alkali metal salt thereof may be mixed and used. The alkali metal may be Na, K or Li.
[0141] The dry binder may be a polymer material capable of fiberization, and may be, for example, polytetrafluoroethylene, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer, polyethylene oxide, and / or (eg, any appropriate) combinations thereof.
[0142] Conductive Materials
[0143] In one or more embodiments, a conductive material (e.g., an electronic conductor) may be included to provide and / or improve electrode conductivity, and any conductive material may be used as a conductive material unless it causes a chemical change. Non-limiting examples of conductive materials may include: carbon-based materials such as natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, carbon nanofiber, carbon nanotube, etc.; metal-based materials including metal powders or metal fibers of copper, nickel, aluminum, silver, etc.; conductive polymers such as polyphenylene derivatives; and / or (e.g., any suitable) mixtures thereof.
[0144] Based on the total weight of 100wt% of the negative electrode active material layer, the content (e.g., amount) of the negative electrode active material may be about 95wt% to about 99.5wt%, and based on the total weight of 100wt% of the negative electrode active material layer, the content (e.g., amount) of the binder may be about 0.5wt% to about 5wt%. For example, in one or more embodiments, based on the total weight of 100wt% of the negative electrode active material layer, the negative electrode active material layer may include about 90wt% to about 99wt% of the negative electrode active material, about 0.5wt% to about 5wt% of the binder, and about 0wt% to about 5wt% of the conductive material.
[0145] Negative electrode current collector
[0146] The negative electrode current collector may include, for example, indium (In), copper (Cu), magnesium (Mg), stainless steel, titanium (Ti), iron (Fe), cobalt (Co), nickel (Ni), zinc (Zn), aluminum (Al), germanium (Ge), lithium (Li) or an alloy thereof, and may be in the form of (or provided in) foil, sheet or foam. The thickness of the negative electrode current collector may be, for example, about 1 μm to about 20 μm, about 5 μm to about 15 μm or about 7 μm to about 10 μm.
[0147] Electrolyte
[0148] In one or more embodiments, the electrolyte for a rechargeable lithium battery may be an electrolyte that may include a non-aqueous organic solvent and a lithium salt.
[0149] The non-aqueous organic solvent is used as a medium for transmitting ions participating in the electrochemical reaction of the battery. The non-aqueous organic solvent may include carbonate solvents, ester solvents, ether solvents, ketone solvents, alcohol solvents, aprotic solvents and / or (for example, any appropriate) combinations thereof.
[0150] Carbonate solvents may include dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), ethyl methyl carbonate (MEC), ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), etc. Ester solvents may include methyl acetate, ethyl acetate, n-propyl acetate, dimethyl acetate, methyl propionate, ethyl propionate, decanoic acid lactone, mevalonate lactone, valerolactone, caprolactone, etc. Ether solvents may include dibutyl ether, tetraethylene glycol dimethyl ether, diethylene glycol dimethyl ether, dimethoxyethane, 2-methyltetrahydrofuran, 2,5-dimethyltetrahydrofuran, tetrahydrofuran, etc. In one or more embodiments, ketone solvents may include cyclohexanone, etc. Alcohol solvents may include ethanol, isopropanol, etc., and aprotic solvents may include nitriles (such as R-CN (wherein R is a C2-C20 straight chain, branched or cyclic hydrocarbon group, and may include a double bond, an aromatic ring or an ether bond, etc.)); amides (such as dimethylformamide); dioxolanes (such as 1,3-dioxolane, 1,4-dioxolane, etc.); cyclopentane sulfone, etc.
[0151] The non-aqueous organic solvent may be used alone or in a mixture of two or more types (kinds), and if (for example, when) two or more types (kinds) are used in a mixed form, the mixing ratio may be suitably or appropriately adjusted according to the desired or appropriate battery performance, which is well known to those skilled in the art.
[0152] If (for example, when) a carbonate-based solvent is used, a cyclic carbonate and a chain carbonate may be mixed and used, and the cyclic carbonate and the chain carbonate may be mixed in a volume ratio of about 1:1 to about 1:9.
[0153] In one or more embodiments, the non-aqueous organic solvent may further include an aromatic hydrocarbon organic solvent. For example, in some embodiments, a carbonate-based solvent and an aromatic hydrocarbon organic solvent may be mixed and used in a volume ratio of about 1:1 to about 30:1.
[0154] In one or more embodiments, the electrolyte may further include vinyl ethylene carbonate, vinylene carbonate, or ethylene carbonate-based compounds to improve the battery cycle life.
[0155] Non-limiting examples of the ethylene carbonate-based compound may include fluoroethylene carbonate, difluoroethylene carbonate, chloroethylene carbonate, dichloroethylene carbonate, bromoethylene carbonate, dibromoethylene carbonate, nitroethylene carbonate, and cyanoethylene carbonate.
[0156] The lithium salt dissolved in the non-aqueous organic solvent supplies lithium ions in the rechargeable lithium battery, ensures the basic operation of the rechargeable lithium battery, and improves the transport of lithium ions between the positive electrode and the negative electrode. Non-limiting examples of the lithium salt may include a selected from LiPF 6 , LiBF 4 、LiSbF 6 、LiAsF 6 、LiClO 4 、LiAlO 2 、LiAlCl 4 、LiPO 2 F 2 、LiCl、LiI、LiN(SO 3 C 2 F 5 ) 2 、Li(FSO 2 ) 2 N(lithium bis(fluorosulfonyl)imide; LiFSI), LiC 4 F 9 SO 3 、LiN(C x F 2x+1 SO 2 )(C y F 2y+ 1 SO 2 )(wherein x and y are integers of 1 to 20), at least one of lithium trifluoromethanesulfonate, lithium tetrafluoroethanesulfonate, lithium difluorobis(oxalato)phosphate (LiDFBOP) and lithium bis(oxalato)borate (LiBOB).
[0157] The concentration of the lithium salt may be in the range of about 0.1 M to about 2.0 M. When the concentration of the lithium salt is within the above range, the electrolyte has suitable or appropriate ion conductivity and viscosity, and thus excellent or appropriate performance may be achieved, and lithium ions may be efficiently moved.
[0158] Diaphragm
[0159] Depending on the type or kind of the rechargeable lithium battery, the separator may be present between the positive electrode and the negative electrode. The separator may include a polyethylene separator, a polypropylene separator, a polyvinylidene fluoride separator, or a multilayer film of two or more layers thereof (such as a polyethylene / polypropylene two-layer separator, a polyethylene / polypropylene / polyethylene three-layer separator, a polypropylene / polyethylene / polypropylene three-layer separator, etc.).
[0160] The membrane may include a porous substrate and a coating on one or both surfaces (e.g., opposite surfaces) (e.g., on both surfaces (e.g., opposite surfaces)) of the porous substrate, the coating comprising an organic material, an inorganic material and / or a combination thereof (e.g., any suitable one).
[0161] The porous substrate may be a polymer film formed by: any one selected from the group consisting of polymers polyolefins (such as polyethylene and / or polypropylene), polyesters (such as polyethylene terephthalate and / or polybutylene terephthalate), polyacetals, polyamides, polyimides, polycarbonates, polyether ketones, polyarylether ketones, polyetherimides, polyamideimides, polybenzimidazoles, polyethersulfones, polyphenylene oxides, cyclic olefin copolymers, polyphenylene sulfide, polyethylene naphthalate, glass fibers, and polytetrafluoroethylene (e.g., Teflon); or copolymers or mixtures of two or more thereof.
[0162] The porous substrate may have a thickness of about 1 μm to about 40 μm, for example, about 1 μm to about 30 μm, about 1 μm to about 20 μm, about 5 μm to about 15 μm, or about 10 μm to about 15 μm.
[0163] The organic material may include a (meth)acryl-based copolymer, which includes: a first structural unit derived from (meth)acrylamide; and a second structural unit including at least one of a structural unit derived from (meth)acrylic acid or (meth)acrylate and a structural unit derived from (meth)acrylamide sulfonic acid or its salt.
[0164] The inorganic material may include a 2 O 3 、SiO 2 、TiO 2 SnO 2 、CeO 2 , MgO, NiO, CaO, GaO, ZnO, ZrO 2 , Y2 O 3 、SrTiO 3 、BaTiO 3 Mg(OH) 2 , boehmite and / or (for example, any appropriate) combination thereof, but the embodiments of the present disclosure are not limited thereto. The average particle size (D 50 ) may be from about 1 nm to about 2000 nm, for example, from about 100 nm to about 1000 nm or from about 100 nm to about 700 nm.
[0165] An organic material and an inorganic material may be mixed in one coating layer, or a coating layer including an organic material and a coating layer including an inorganic material may be stacked.
[0166] The coating layer may have a thickness of about 0.5 μm to about 20 μm, for example, about 1 μm to about 10 μm or about 1 μm to about 5 μm.
[0167] Examples and comparative examples of the present disclosure are described in more detail herein.However, the following examples are merely examples of the present disclosure, and the present disclosure is not limited to the following examples.
[0168] Example 1
[0169] 1. Preparation of positive electrode active material
[0170] (1) Preparation of the first positive electrode active material
[0171] Ni 0.75 Mn 0.23 Al 0.02 (OH) 2 and LiOH in a molar ratio of 1:1.05, and then subjected to a preliminary heat treatment at 850° C. for 8 hours in an oxygen atmosphere to prepare a first composite oxide in the form of secondary particles having Li 1.05 Ni 0.75 Mn 0.23 Al 0.02 O 2 composition.
[0172] After aluminum sulfate is mixed with a distilled water solvent, a first composite oxide is added thereto and then mixed for 20 to 60 minutes. In this article, the aluminum content (e.g., amount) in aluminum sulfate is designed to be 1.0 mol% based on 100 mol% of the total metals other than lithium in the final first positive electrode active material. After removing the solvent from the mixed solution and drying at 190 ° C, zirconium oxide is added thereto, and then reheated at 825 ° C for 8 hours under an oxygen atmosphere to obtain the first positive electrode active material. In zirconium oxide, the zirconium content (e.g., amount) is designed to be 0.2 mol% based on 100 mol% of the total metals other than lithium in the final first positive electrode active material. Figure 2 The SEM image of the first positive electrode active material is shown. The average particle size (D 50 ) is about 14μm.
[0173] (2) Preparation of the Second Positive Electrode Active Material
[0174] Ni 0.75 Mn 0.25 (OH) 2 , LiOH and Al 2 O 3 The mixture was mixed in a molar ratio of 1:1:0.02 and then subjected to a preliminary heat treatment at 850°C for 8 hours in an oxygen atmosphere to prepare a LiNi 0.75 Mn 0.23 Al 0.02 O 2 The composition and average particle size (D 50 ) is a second composite oxide in the form of individual particles of about 3 μm.
[0175] After aluminum sulfate and yttrium nitrate are mixed with distilled water solvent, the second composite oxide is added thereto and then mixed for 20 to 60 minutes. In this article, based on 100wt% of the total metals other than lithium in the final second positive electrode active material, the aluminum content (e.g., amount) in aluminum sulfate is designed to be 0.4mol%, and based on 100wt% of the total metals other than lithium in the final second positive electrode active material, the yttrium content (e.g., amount) in yttrium nitrate is designed to be 0.1mol%. After removing the solvent from the mixed solution and drying at 190°C, a reheating treatment of 8 hours is carried out at 825°C under an oxygen atmosphere to prepare the second positive electrode active material. Figure 3 The SEM image of the second positive electrode active material is shown. The average particle size (D 50 ) is about 3.5μm.
[0176] (3) Preparation of the Third Positive Electrode Active Material
[0177] Mn 3 O 4 , Li 2 CO 3 、Al 2 O 3 and MgCO 3 The mixture was mixed in a molar ratio of 1:1:0.005:0.005 and then subjected to a preliminary heat treatment at 700°C for 8 hours in an oxygen atmosphere to prepare a LiMn 1.99 Mg 0.005 Al 0.005 O 4 The composition and average particle size (D 50 ) is a third composite oxide in the form of a plurality of individual particles of about 7.5 μm. The third composite oxide and Al 2 O 3 Mixing was performed so that the content (eg, amount) of Al was 0.1 mol% based on 100 wt% of total metals excluding lithium in the final third positive electrode active material, and reheating treatment was performed at 650°C for 6 hours in an oxygen atmosphere to prepare a third positive electrode active material.
[0178] Figure 4 and Figure 5 Each shows a SEM image of a third positive electrode active material.
[0179] (4) Preparation of the final positive electrode active material
[0180] Based on the total amount of the final positive electrode active material, 70 wt % of the first positive electrode active material, 20 wt % of the second positive electrode active material, and 10 wt % of the third positive electrode active material were mixed to prepare the final positive electrode active material.
[0181] 2. Preparation of positive electrode
[0182] Based on the total amount of the positive electrode active material layer slurry, 98.5wt% of the positive electrode active material, 1.0wt% of the polyvinylidene fluoride binder and 0.5wt% of the carbon nanotube conductive material are mixed to prepare the positive electrode active material layer slurry, and the positive electrode active material layer slurry is coated on an aluminum foil positive electrode current collector, and then dried and pressed to prepare a positive electrode. The density of the positive electrode active material layer in the final pressed positive electrode is about 3.52g / cc.
[0183] 3. Preparation of rechargeable lithium battery cells
[0184] Based on the total amount of the negative electrode active material layer slurry, 97.5wt% of graphite negative electrode active material, 1.5wt% of carboxymethyl cellulose and 1wt% of styrene butadiene rubber in an aqueous solvent were mixed to prepare a negative electrode active material layer slurry. The negative electrode active material layer slurry was coated on a copper foil negative electrode current collector, and then dried and pressed to prepare a negative electrode.
[0185] A polytetrafluoroethylene membrane was used, and 1 M LiPF 6 The electrolyte prepared by dissolving in a mixed solvent of ethylene carbonate and dimethyl carbonate in a volume ratio of 3:7 was used to prepare a rechargeable lithium battery cell (coin-type battery cell) in a conventional manner.
[0186] Example 2
[0187] A positive electrode and a rechargeable lithium battery cell were prepared in substantially the same manner as in Example 1, except that the positive electrode active material was prepared by mixing 70 wt % of the first positive electrode active material, 15 wt % of the second positive electrode active material, and 15 wt % of the third positive electrode active material.
[0188] Comparative Example 1
[0189] A positive electrode and a rechargeable lithium battery cell were prepared in substantially the same manner as in Example 1, except that the positive electrode active material was prepared by mixing 70 wt % of the first positive electrode active material and 30 wt % of the second positive electrode active material without the third positive electrode active material.
[0190] Comparative Example 2
[0191] A positive electrode and a rechargeable lithium battery cell were prepared in substantially the same manner as in Example 1, except that the positive electrode active material was prepared by mixing 70 wt % of the first positive electrode active material and 30 wt % of the third positive electrode active material without the second positive electrode active material.
[0192] For better understanding, the design details of the positive electrode active materials of Examples and Comparative Examples are briefly shown in Table 1.
[0193] (Table 1)
[0194]
[0195]
[0196] Evaluation Example 1
[0197] At 25° C., each of the rechargeable lithium battery cells of the embodiment and the comparative example was charged to an upper limit voltage of 4.45V at a constant current of 0.2C, charged to a constant voltage of 0.05C, and then discharged to a cutoff voltage of 3.0V at 0.2C for initial charging and discharging. Subsequently, at 45° C., each of these battery cells was charged 50 times or more at 1.0C in a voltage range of 3.0V to 4.45V, and discharged at 1.0C to calculate the ratio of the 50th cycle discharge capacity to the initial discharge capacity (i.e., cycle life), and the results are shown in Table 1.
[0198] In addition, the average voltage at SOC (State of Charge) 50% during initial discharge was measured, and the results are shown in Table 1.
[0199] In addition, the density of the positive electrode active material layer in the positive electrode in the pressed state of the Examples and Comparative Examples is shown in Table 1.
[0200] Referring to Table 1, the Examples each exhibited a much higher density of the positive electrode active material layer in the positive electrode and a much higher average voltage than the Comparative Examples, thus producing desirable (eg, excellent or appropriate) cycle-life characteristics during driving at a high voltage of 4.45V.
[0201] In the present disclosure, "not including one or any 'component'", "excluding one or any 'component'", "no 'component'", etc. means that the "component" is not added, selected or utilized as a component in the composition / element / structure. However, in some embodiments, due to other impurities and / or external factors, the "component" may still be included in an amount less than the appropriate amount.
[0202] As used herein, the terms "substantially," "about," and similar terms are used as terms of approximation rather than as terms of degree, and are intended to account for the inherent deviations in measured or calculated values that would be recognized by one of ordinary skill in the art. Also, "about" or "approximately" as used herein include the stated value and mean within an acceptable range of deviation for the particular value determined by one of ordinary skill in the art taking into account the measurement in question and the errors associated with the measurement of the particular quantity (i.e., the limitations of the measurement system). For example, "about" may mean within one or more standard deviations, or within ±30%, ±20%, ±10%, or ±5% of the stated value.
[0203] Any numerical range set forth in this article is intended to include all sub-ranges of the same numerical precision contained in the range of the setting forth. For example, the range of "1.0-10.0" is intended to include all sub-ranges (and end values) between the minimum value 1.0 set forth and the maximum value 10.0 set forth, that is, a minimum value equal to or greater than 1.0 and a maximum value equal to or less than 10.0, such as, for example, 2.4-7.6. Any maximum numerical limit set forth herein is intended to include all lower numerical limits contained therein, and any minimum numerical limit set forth in this specification is intended to include all higher numerical limits contained therein. Accordingly, the applicant reserves the right to modify this specification (including claims) to explicitly set forth any sub-ranges contained in the range explicitly set forth herein.
[0204] The battery management system (BMS) device and / or any other related device or component according to the embodiments of the present invention described herein may be implemented using any appropriate hardware, firmware (e.g., a dedicated integrated circuit), software, or a combination of software, firmware, and hardware. For example, the various components of the device may be formed on an integrated circuit (IC) chip or on a separate IC chip. In addition, the various components of the device may be implemented on a flexible printed circuit film, a tape carrier package (TCP), or a printed circuit board (PCB), or formed on a substrate. In addition, the various components of the device may be processes or threads running on one or more processors in one or more computing devices, executing computer program instructions and interacting with other system components to perform the various functions described herein. The computer program instructions are stored in a memory, which may be implemented in a computing device using a standard memory device, such as, for example, a random access memory (RAM). The computer program instructions may also be stored in other non-temporary computer-readable media (such as, for example, a CD-ROM, a flash drive, etc.). Moreover, those skilled in the art should recognize that, without departing from the scope of the present disclosure, the functions of various computing devices may be combined or integrated into a single computing device, or the functions of a dedicated computing device may be distributed on one or more other computing devices.
[0205] Although the present disclosure has been described in conjunction with what are presently considered to be practical example embodiments, it should be understood that the present disclosure should not be limited to the disclosed embodiments. Instead, the present disclosure is intended to cover one or more suitable modifications and equivalent arrangements included within the spirit and scope of the claims and their equivalents.
Claims
1. A positive electrode active material comprising: a first positive electrode active material comprising a lithium nickel manganese-based composite oxide having a nickel content of greater than or equal to 60 mol % based on 100 mol % of the total metals other than lithium in the first positive electrode active material and in the form of a plurality of secondary particles each including a plurality of primary particles aggregated, a second positive electrode active material in the form of a plurality of individual particles including a lithium nickel manganese-based composite oxide having a nickel content of 60 mol % or more based on 100 mol % of the total metals other than lithium in the second positive electrode active material, and The third positive electrode active material is in the form of a plurality of particles including a lithium manganese-based oxide.
2. The positive electrode active material according to claim 1, wherein The average particle size D of the secondary particles of the first positive electrode active material 50 10μm~20μm, The average particle size D of the single particles of the second positive electrode active material 50 0.5μm~8μm, and The average particle size D of the particles of the third positive electrode active material 50 5μm~12μm.
3. The positive electrode active material according to claim 1, wherein Based on 100 wt% of the total weight of the first positive electrode active material, the second positive electrode active material and the third positive electrode active material, The amount of the first positive electrode active material is 60 wt% to 90 wt%, The amount of the second positive electrode active material is 5 wt% to 35 wt%, and The amount of the third positive electrode active material is 5 wt % to 35 wt %.
4. The positive electrode active material according to claim 1, wherein Based on 100 wt% of the total weight of the first positive electrode active material, the second positive electrode active material and the third positive electrode active material, The amount of the first positive electrode active material is 60wt% to 85wt%, The amount of the second positive electrode active material is 10 wt% to 25 wt%, and The amount of the third positive electrode active material is 5 wt % to 20 wt %.
5. The positive electrode active material according to claim 1, wherein The lithium nickel manganese composite oxide of the first positive electrode active material and the lithium nickel manganese composite oxide of the second positive electrode active material are the same or different, and each independently has a nickel content of 60 mol% to 80 mol% based on 100 mol% of total metals other than lithium in each corresponding lithium nickel manganese composite oxide.
6. The positive electrode active material according to claim 1, wherein The lithium nickel manganese-based composite oxide of the first positive electrode active material and the lithium nickel manganese-based composite oxide of the second positive electrode active material each independently further include aluminum in addition to nickel and manganese, and The aluminum content in each of the corresponding lithium nickel manganese aluminum-based composite oxides is 1 mol% to 3 mol% based on 100 mol% of total metals except lithium in each of the corresponding lithium nickel manganese aluminum-based composite oxides.
7. The positive electrode active material according to claim 1, wherein The lithium nickel manganese based composite oxide of the first positive electrode active material and the lithium nickel manganese based composite oxide of the second positive electrode active material each independently have a cobalt content of 0 mol% to 0.01 mol% based on 100 mol% of total metals other than lithium in each corresponding lithium nickel manganese based composite oxide, and The lithium manganese based oxide of the third positive electrode active material has a cobalt content of 0 mol % to 0.01 mol % based on 100 mol % of total metals except lithium in the lithium manganese based composite oxide.
8. The positive electrode active material according to claim 1, wherein The lithium nickel manganese composite oxide of the first positive electrode active material and the lithium nickel manganese composite oxide of the second positive electrode active material are each independently represented by Chemical Formula 1: Chemical formula 1 Li a1 Ni x1 Mr y1 Al z1 M 1 w1 O 2-b1 X b1 , In Chemical Formula 1, 0.9≤a1≤1.8, 0.6≤x1≤0.8, 0.1≤y1≤0.4, 0≤z1≤0.03, 0≤w1≤0.3, 0.9≤x1+y1+z1+w1≤1.1, and 0≤b1≤0.1, M 1 is one or more elements selected from B, Ba, Ca, Ce, Cr, Fe, Mg, Mo, Nb, Si, Sn, Sr, Ti, V, W, Y and Zr, and X is one or more elements selected from F, P and S.
9. The positive electrode active material according to claim 8, wherein In Chemical Formula 1, 0.6≤x1≤0.8, 0.1≤y1≤0.39, 0.01≤z1≤0.03, and 0≤w1≤0.29 are satisfied.
10. The positive electrode active material according to claim 1, wherein The first positive electrode active material further includes a coating layer on a surface of each of the secondary particles and including aluminum.
11. The positive electrode active material according to claim 10, wherein The coating layer may have an aluminum content of 0.1 mol% to 2 mol% based on 100 mol% of total metals excluding lithium in the first positive electrode active material.
12. The positive electrode active material according to claim 10, wherein The coating further includes zirconium, yttrium, or a combination thereof.
13. The positive electrode active material according to claim 12, wherein Based on 100 mol % of the total metals other than lithium in the first positive electrode active material, The coating comprises: 0.05 mol% to 1 mol% zirconium; and / or 0.05mol% to 1mol% yttrium.
14. The positive electrode active material according to claim 10, wherein The coating layer of the first positive electrode active material has the form of a shell continuously surrounding the surface of each of the secondary particles.
15. The positive electrode active material according to claim 10, wherein The coating layer of the first positive electrode active material has a thickness of 30 nm to 500 nm.
16. The positive electrode active material according to claim 10, wherein The first positive electrode active material further includes a grain boundary coating portion on the surface of each of the primary particles inside each of the secondary particles and containing aluminum.
17. The positive electrode active material according to claim 1, wherein The second positive electrode active material further includes a coating layer on a surface of each of the plurality of individual particles and including aluminum.
18. The positive electrode active material according to claim 17, wherein The coating layer may have an aluminum content of 0.1 mol% to 2 mol% based on 100 mol% of total metals excluding lithium in the second positive electrode active material.
19. The positive electrode active material according to claim 17, wherein The coating of the second positive electrode active material has the form of a shell continuously surrounding the surface of the single particle.
20. The positive electrode active material according to claim 17, wherein the thickness of the coating of the second positive electrode active material is 30 nm to 500 nm.
21. The positive electrode active material according to claim 17, wherein the coating of the second positive electrode active material further comprises yttrium.
22. The positive electrode active material according to claim 21, wherein based on 100 mol% of the total metals other than lithium in the second positive electrode active material, the yttrium content of the coating is 0.1 mol% to 1 mol%.
23. The positive electrode active material according to claim 21, wherein in the coating of the second positive electrode active material, the aluminum exists in the form of a continuous film, and the yttrium exists in the form of islands.
24. The positive electrode active material according to claim 21, wherein the second positive electrode active material comprises a first coating on the surface of the single particle and containing aluminum, and a second coating on the first coating and containing yttrium.
25. The positive electrode active material according to claim 1, wherein the third positive electrode active material has the form of a plurality of secondary particles each comprising a plurality of primary particles aggregated together.
26. The positive electrode active material according to claim 1, wherein in addition to manganese, the lithium manganese-based oxide of the third positive electrode active material further comprises aluminum, magnesium, yttrium, or a combination thereof.
27. The positive electrode active material according to claim 1, wherein the lithium manganese-based oxide of the third positive electrode active material is represented by Chemical Formula 3: Chemical Formula 3 Li a3 Mn x3 M 3 y3 O 4-b3 X b3 , In Chemical Formula 3, 0.9 ≤ a3 ≤ 1.8, 1.7 ≤ x3 ≤ 2, 0 ≤ y3 ≤ 0.3, 1.9 ≤ x3 + y3 ≤ 2.1, and 0 ≤ b3 ≤ 0.1, M 3 is one or more elements selected from the group consisting of Al, B, Ba, Ca, Ce, Cr, Fe, Mg, Mo, Nb, Si, Sn, Sr, Ti, V, W, Y and Zr, and X is one or more elements selected from F, P, and S.
28. The positive electrode active material according to claim 27, wherein the lithium manganese-based oxide of the third positive electrode active material is represented by Chemical Formula 4: Chemical Formula 4 Li a4 Mn x4 Al y4 Mg z4 M 4 w4 O 4-b4 X b4 , In Chemical Formula 4, 0.9 ≤ a4 ≤ 1.8, 1.7 ≤ x4 < 2.0, 0 < y4 ≤ 0.015, 0 < z4 ≤ 0.010, 0 ≤ w4 < 0.3, 1.9 ≤ x4 + y4 + z4 + w4 ≤ 2.1, and 0 ≤ b4 ≤ 0.1, M 4 is one or more elements selected from B, Ba, Ca, Ce, Cr, Fe, Mo, Nb, Si, Sn, Sr, Ti, V, W, Y and Zr, and X is one or more elements selected from F, P, and S.
29. The positive electrode active material according to claim 1, wherein the third positive electrode active material further comprises a coating on the surface of each of the plurality of particles and containing aluminum.
30. The positive electrode active material according to claim 29, wherein based on 100 mol% of the total metals other than lithium in the third positive electrode active material, the amount of aluminum in the coating is 0.01 mol% to 1 mol%.
31. A positive electrode, comprising a positive electrode current collector, and A positive electrode active material layer is provided on the positive electrode current collector, wherein the positive electrode active material layer comprises the positive electrode active material according to any one of claims 1 to 30.
32. The positive electrode of claim 31, wherein The positive electrode active material layer has a density of 3.5 g / cc to 3.7 g / cc.
33. A rechargeable lithium battery comprising The positive electrode according to claim 31 or 32, negative electrode, and Electrolyte.
34. The rechargeable lithium battery of claim 33, wherein a charging voltage of the rechargeable lithium battery is 4.3V to 4.6V.
Citation Information
Cited By
Positive electrode active material, positive plate, battery, battery pack, electric equipment and quality control method of positive electrode active material
CN121260785A
Positive electrode active material, positive electrode sheet, battery, battery pack, power tool, quality control method for positive electrode active material
CN121260785B